Compassion-Focused Group Therapy for Treatment-Resistant OCD: Initial Evaluation Using a Multiple Baseline Design - Petrocchi, Nicola; Cosentino, Teresa; Pellegrini, Valerio; Femia, Giuseppe; D’Innocenzo, Antonella; Mancini, Francesco (Frontiers in Psychology, 2021)
Obsessive-compulsive disorder (OCD) is a debilitating mental health disorder that can easily become a treatment-resistant condition. Although effective therapies exist only about half of the patients seems to benefit from them when we consider treatment refusal, dropout rates and residual symptoms. Thus, providing effective augmentation to standard therapies could improve existing treatments. Group compassion focused interventions have shown promise for reducing depression, anxiety and avoidance related to various clinical problems, but this approach has never been evaluated for OCD individuals. However, cultivating compassion for self and others seems crucial for OCD patients, given the accumulating research suggesting that fear of guilt, along with isolation and self-criticism, can strongly contribute to the development and maintenance of OCD. The primary aim of this pilot study was to evaluate the acceptability, tolerability, and efficacy of an 8-week group compassion focused intervention for reducing OCD symptoms, depression, fear of guilt and self-criticism, and increase common-humanity and compassionate self-reassuring skills in treatment-resistant OCD patients. Using a multiple baseline experimental design, the intervention was evaluated in a sample of OCD patients (N = 8) who had completed at least 6 months of CBT treatment for OCD, but who continued to suffer from significant symptoms. Participants were randomized to different baseline assessment lengths, then they received 8 weekly, 120 minute group sessions of compassion focused therapy for OCD (CFT-OCD), and then they were tested again at post-treatment and at one-month follow up. Despite the adverse external circumstances (post treatment and follow-up data collection were carried out, respectively, at the beginning and in the middle of the Italian lockdown due to the COVID-19 pandemic), by the end of treatment all participants demonstrated reliable decreases in OCD symptom, and these improvements were maintained at 4-week follow-up for 7 of 8 participants. The intervention was also associated with improvements in fear of guilt, self-criticism and self-reassurance but less consistent improvements in depression and common humanity. Participants reported high levels of acceptability of and satisfaction with the intervention. Results suggest that the intervention may be beneficial as either a stand-alone treatment or as an augmentation to other treatments.